Dampak COVID-19 Terhadap Pelayanan KIA di Kota Cilegon - Zulfa Kevaladandra; Evi Martha (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: The COVID-19 pandemic has challenged maternal and child health services in all regions of Indonesia, including the city of Cilegon. Various efforts have been made by the Cilegon City Health Office to suppress the decline in MCH services. The purpose of this study was to determine the impact of COVID-19 on MCH services in Cilegon City.Methods: This article used a qualitative descriptive method by collecting data through focus group discussions (FGD) in the second week of October 2020. The informants of this study collected by purposive sampling with the number of informants. 4 informants, including the Head of the Cilegon City Health Office, the Head of the Family Health Section (Kesga), and 2 Kesga staff.Results: The results showed that there were 7 indicators affected by COVID-19 in the city of Cilegon, including K1 coverage, K4 coverage, delivery assistance at health facilities, maternal mortality rate (MMR), neonatal visits, complete basic immunization services, and monitoring of toddler growth and development. The cause of the obstruction of MCH services was the existence of the PSBB policy and the concerns of the public and health workers of contracting the SARS-CoV-2 virus.Conclusion: Several inovasions made by the Cilegon City Health Office include implementing health protocols in health services outside buildings, making appointments for antenatal and immunization services, conducting home visits, conducting classes for pregnant women and toddlers through live streaming, and providing isolation places for OTGs. It can be concluded that the COVID-19 pandemic has caused a challenges in MCH services. However, various efforts have also been made to increase the coverage of MCH services and improve maternal and child health in the city of Cilegon.